Toward the enhancement of derivatives trading in the CARICOM Sub Region - Roopnarine, Karen Anne ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2005)
Seeks to determine the feasibility of developing the capital markets of the CARICOM Sub Region through the enhancement of derivatives trading in the two largest financial markets in the region viz. Trinidad & Tobago and Jamaica.